Priming Effects and Strategic Influences in Social Tagging. (3rd March 2016) - Bodoff, David; Vaknin, Eran
Abstract : In many social tagging systems, users can see the tags already created by others. Prior research has shown that this exposure leads users to create tags that are semantically related to the previous ones. We investigate two possible mechanisms through which this occurs, semantic priming and strategic choice. Semantic priming occurs when an existing tag subconsciously primes the user's mind to suggest semantically related tags. In an experiment, no such effect is found, in contrast to prior research. A follow-up study shows that whether semantic priming occurs depends on whether the person uses others' previously created tags or is just passively exposed to them. The second type of influence, strategic choice, occurs in ESP-type settings. It refers to behavior in which a user chooses words that are semantically related to an existing tag in order to increase the chances of matching one's partner. Experimental results provide clear evidence of this strategic influence. In a follow-up study, we demonstrate that there is a meaningful difference in the tag sets that are created under the influence of strategic choice. Our work sheds light on the conditions and mechanisms through which existing tags influence subsequent tagging behavior.